Application of Technological Automation and Digitalization of Promotional Efforts in the Home Industry of Wickerwork in Jombang Regency: PAR Method - Siti Zahro; Tri Sagirani; Faizal Susilo Hadi; Hany Mustikasari; Hedi Amelia Bella Cintya; Nugraha Nugraha; Didik Nurhadi; Matthew Lucky Natanael; Gabriella Haldis Adriani; Medhita Gunawan Putri; Dewi Anggraini Tjandra; Felix Dian Nugroho; Oka Wardana; Rizky Alifio Muhammad (Smart Society, 2026)
The wickerwork home industry in Jombang Regency, which utilizes screw pine and bamboo, plays an important role in local employment. However, its development remains constrained by manual production processes and limited marketing strategies. This study aims to examine the implementation of technological automation and the digitalization of promotional efforts in wickerwork home industries using a Participatory Action Research (PAR) approach, consisting of identification, planning, action, observation, and evaluation stages. The program involved two home industries, including owners and employees, in adopting simple automation technologies and digital marketing practices. The results indicate that the application of automation technology improved production efficiency and enabled businesses to better meet customer demand. In addition, digital promotion training covering product photography, content creation, and the use of AI tools enhanced marketing reach through social media, contributing to increased national-level demand. This study highlights that integrating automation and digital marketing can strengthen the competitiveness of small-scale industries. However, sustained mentoring and multi-stakeholder support are essential to ensure long-term impact, expand employment opportunities, and promote business sustainability.